FORMATION OF A MOTIVATIONAL-COMMUNICATIVE ENVIRONMENT THROUGH INTERACTIVE TEACHING TECHNOLOGIES IN TEACHING ENGLISH TO PRESCHOOL STUDENTS - Yuldasheva Umidaxon Makhmudovna (Web of Journals Publishing, 2025)
The article analyzes pedagogical and psychological foundations of motivation in foreign language teaching within the context of modernization of Uzbekistan's educational system. The research examines two main types of motivation – "direct" and "mediated" motivation. Structural components of motivational space determining the effectiveness of foreign language acquisition are systematically studied: cultural, communicative, social and academic motives. The significance of motivational factors in developing students' critical and creative thinking skills based on competency approach is substantiated. Research findings prove dialectical relationship between motivation and learning environment.
Keywords: Motivation, foreign language teaching, motivational space, pedagogical psychology, competency approach, cognitive motives, communicative motives, educational modernization, motivational structure, learning activity.